Proposal for public policies regarding the promotion of online passport scheduling - Luchenciuc Elena-Georgiana (Technium Social Sciences Journal, 2020)
About 70% of Romanians who need to get their passports renewed wait in a queue instead of scheduling an online scheduling. The truth is that many forget that the time of waiting for hours on end in queues has set, and this aspect should disappear from the conception of many people who have experienced hard times many years ago. At a regular queue, a Romanian stays for at least 2 hours if he has not reached among the first persons, which is not at all beneficial for them, but neither for the employees. The objective of the public policy proposal is to promote online scheduling for passports by: reducing queues on passports, reducing the stress of employees who work directly with the public and maintaining a harmonious connection between people and the website https://epasapoarte.ro.